A Review of Prognosis Model Associated With Cardiogenic Shock After Acute Myocardial Infarction - Wang, Jingyue; Shen, Botao; Feng, Xiaoxing; Zhang, Zhiyu; Liu, Junqian; Wang, Yushi (Frontiers in Cardiovascular Medicine, 2021)
Objective: Cardiogenic shock seriously affects the survival rate of patients. However, few prognostic models are concerned with the score of cardiogenic shock, and few clinical studies have validated it. Methods: Cardiogenic shock, severe case, prognosis score, myocardial infarction, and external verification were used as the search terms to search PubMed, Embase, Web of Science, Cochrane, EBSCO (Medline), Scopus, BMC, NCBI, Oxford Academy, Science Direct, and other databases. Results and conclusions: The IABP-SHOCK II score and CardShock score are more suitable for evaluating the prognosis of cardiogenic shock after acute myocardial infarction. However, with the development of molecular omics and the need for optimal treatment of cardiogenic shock in clinics, establishing a prognostic model with higher differentiation and coincidence rates is urgently required.